MACROECONOMIC DETERMINANTS OF STOCK MARKET VOLATILITY: AN EMPIRICAL STUDY OF MALAYSIA AND INDONESIA - Lida Nikmanesh; Abu Hassan Shaari Mohd Nor (Asian Academy of Management Journal, 2016)
The present study examines the relationship between stock market volatility and the volatility of macroeconomic variables in Malaysia and Indonesia. The relationship is examined through the analysis of the monthly data concerning stock indices and macroeconomic variables in Malaysia and Indonesia for the period of 1998 until 2013. Firstly, in order to estimate the conditional volatility of each series, GARCH family models are employed. Secondly, a Seemingly Unrelated Regression (SUR) is utilized to determine whether any significant relationship exists between stock volatility and macroeconomic volatility. The results of the present study provide evidence of a significant relationship between the volatility of stock markets and macroeconomic variables in both countries. In particular, the results indicate that macroeconomic volatility and trade openness explain 81% of stock market volatility in Malaysia; and 75% of stock market volatility in Indonesia. The results of the present study provide more precise information for investors making decisions relating to asset allocation. Additionally, the findings are beneficial for managers and policy makers seeking to reduce the negative effects of stock market volatility on economic performance.